Nitrogen Fixation - Nishibayashi, Yoshiaki (Springer International Publishing : Imprint: Springer, 2017)
This volume presents a review of recent developments in nitrogen fixation using transition metal-dinitrogen complexes in the last decade. The authors are international experts in the corresponding field and each chapter discusses their latest achievements in the preparation of various transition metal-dinitrogen complexes and their reactivity. This volume will be helpful to researchers, teachers, and students who are interested in innovative and sustainable chemistry.
Keywords: Chemistry.; Neurosciences.; Organic chemistry.; elektronické knihy; electronic books